Synthesis, characterization and evaluation of macromonomers used to prepare rheology modifiers for possible improvement of the pigmentation of decorative coatings - Sprong, Ewan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.